Socio Demographic Factors Related to Father Presence in Parenting Adolescents - Edita Pusparatri; Ashri Maulida Rahmawati; Fania Nurul Khoirunnisa; Muhamad Jauhar; Gandi Siwitri; Dwi Febryanto (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Father presence plays a crucial role in the emotional and psychological development of adolescents, yet various socio-demographic factors remain barriers to understanding the significance of fathers' role in parenting. Adolescents who grow up without their fathers are more vulnerable to mental health and social problems, which in turn impact their self-esteem and academic achievement. This study aimed to identify the strongest socio-demographic factors associated with the presence of fathers in the care of adolescents in Kudus District. This study used an observational analytic design with a cross-sectional approach, which was analyzed through the chi-square test and binary logistic regression. The sample consisted of 332 purposively selected high school students. Independent variables included gender difference with the child, parents' marital status, father's education, father's occupation, economic status and family function, while the dependent variable was the level of father’s presence in parenting. The results of the analysis showed that family function in parenting is the strongest social factor that positively influences father presence in adolescent parenting (OR = 6.651, p < 0.05). In addition, the demographic factor of marital status also positively influenced father’s presence in adolescent care (OR = 2.447, p < 0.05). Meanwhile, gender differences between father and child, father's education level, father's occupation, and economic status did not have a significant correlation. The study conclusion emphasizes the importance of integrating family functions in an effort to increase father's participation in parenting, as well as the implications for practice of community health workers, family health programs, and school based family programs.